2019
DOI: 10.1111/cei.13254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibody responses to selected Plasmodium falciparum merozoite surface antigens in mild and cerebral malaria and associations with clinical outcomes

Abstract: Merozoite surface proteins (MSPs) are critical for parasite invasion; they represent attractive targets for antibody-based protection against clinical malaria. To identify protection-associated target MSPs, the present study analysed antibody responses to whole merozoite extract (ME) and to defined MSP recombinant antigens in hospitalized patients from a low endemic urban area as a function of disease severity (mild versus cerebral malaria). Sera from 110 patients with confirmed severe cerebral malaria (CM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Mice selectively deficient in IgM experience greater parasitemia and mortality compared with wild-type mice upon infection with Plasmodium chabaudi , a model for uncomplicated Plasmodium falciparum infection ( Couper et al, 2005 ). Anti-parasite IgM antibodies arising from natural exposure can activate complement to inhibit growth of Plasmodium parasites in vitro and are significantly associated with protection from clinical malaria in human cohorts ( Boyle et al, 2019 ; Kurtovic et al, 2018 ; Mbengue et al, 2019 ). Studies of genetically distinct ethnic groups in West Africa, who experience identical parasite exposure but exhibit different susceptibilities to malaria, have found that resistant and susceptible groups display strongly divergent breadth and magnitude of Plasmodium -specific IgM responses, whereas IgG responses are far more similar between groups ( Bolad et al, 2005 ; Arama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mice selectively deficient in IgM experience greater parasitemia and mortality compared with wild-type mice upon infection with Plasmodium chabaudi , a model for uncomplicated Plasmodium falciparum infection ( Couper et al, 2005 ). Anti-parasite IgM antibodies arising from natural exposure can activate complement to inhibit growth of Plasmodium parasites in vitro and are significantly associated with protection from clinical malaria in human cohorts ( Boyle et al, 2019 ; Kurtovic et al, 2018 ; Mbengue et al, 2019 ). Studies of genetically distinct ethnic groups in West Africa, who experience identical parasite exposure but exhibit different susceptibilities to malaria, have found that resistant and susceptible groups display strongly divergent breadth and magnitude of Plasmodium -specific IgM responses, whereas IgG responses are far more similar between groups ( Bolad et al, 2005 ; Arama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…MSP2 falls into two dimorphic types (Type A and B) represented here by the CH150/9 (type A) and Dd2 (type B) ( 52 ). Despite the level of repetition within the MSP2 proteins studies have used a single allele of MSP2 in combination with other recombinant targets to describe immunity to infection ( 64 ), or have opted for representative sequences from both major dimorphic types as has been done for this study. Lastly, the MSP2-C1 blood stage vaccine is also based on a single representative type from each of the dimorphic classifications (3D7 and Fc27) ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schizonts stage parasites were harvested and lysed in three volumes of sterile distilled water and stored into aliquotes in liquid nitrogen [43]. The MSP3 antigen (clone T9/96) was an E. coli-expressed DG-210 puri ed protein 28 (kind gift from Dr C. Oeuvray) [44].The ELISA assay was performed as previously described [33,44]. The 0703 crude extract was set to 1/3000 dilution by a doseeffect assay using positive control sera.…”
Section: Antigen Preparation and Elisa Assaymentioning
confidence: 99%
“…Results were expressed as optical density (OD) ratio calculated as follow: mean OD sample/mean OD naive serum pool. Sera with an OD ratio > 2 were considered as positive response for prevalence calculations [44] (Mbengue, B et al, 2019). Variations between tests for positive controls should not exceed 20 %.…”
Section: Immunological Parametersmentioning
confidence: 99%